THE INFLUENCE OF AFFECTIVE COMMITMENT, CONTINUANCE COMMITMENT, AND NORMATIVE COMMITMENT TO JOB PERFORMANCE AT PT. BANK INTERNATIONAL INDONESIA MANADO - Joseph, Gladys Citra Beatrix (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
Organization’s success is depends on employee’s performance. Organization Commitment play an important role in organization’s success, where the organization commitment can increase the performance of the employee. This research is purposed to analyze the influence of affective commitment, continuance commitment, and normative commitment to job performance at PT. Bank International Indonesia, Manado. This research used multiple regression analysis and take data from the employees of PT. BII, Manado. Affective commitment, continuance commitment and normative commitment have positive significant relationship on job performance at PT. BII, Manado partially and simultaneously. Commitment in the organization can give benefit for organization itself and for the employees. Employees who have strong commitment in all three dimensions are more productive, loyal, have willingness to achieve the organization’s goal, and still remain with the organization. Keywords: affective commitment, continuance commitment, normative commitment, job performance.